Mixed pyroxenite-peridotite sources for mafic and ultramafic dikes from the Antarctic segment of the Karoo continental flood basalt province - Heinonen, Jussi S.; Luttinen, Arto V.; Riley, Teal R.; Michallik, Radoslaw M. (Lithos, 2014)
Primitive rocks that are related to continental flood basalts are rare, but often reveal crucial information on the ultimate sources of these huge outpourings of mantle-derived magma. Here we present mineral chemical data for mafic and ultramafic dikes from the Antarctic extension of the Jurassic (~180 Ma) Karoo continental flood basalt province that was emplaced during the initial stages of the breakup of the Gondwana supercontinent. We concentrate on two previously recognized high-Ti dike rock suites (Group 3 and Group 4) that exhibit high MgO contents (up to 22 wt. %). Both groups are characterized by Mg-rich olivine phenocrysts (up to Fo90) that are not mantle xenocrysts and indicate derivation from relatively Mg-rich parental magmas. Orthopyroxene is a common phenocryst and groundmass phase indicating emplacement at mid-crustal pressures (2–5 kbar; depth of ~10–20 km). The parental magmas of Group 3 and Group 4 dikes can be associated with pyroxenite sources on the basis of high olivine NiO, high whole-rock Zn/Fe, and low whole-rock CaO. In the case of Group 3 dikes, however, the samples that contain the most Mg-rich olivine also exhibit the mildest pyroxenite fingerprint and indications of an additional olivine-bearing (peridotitic) source component. We propose that the pyroxenite fingerprint of Group 3 and Group 4 dikes reflects relatively low-degree melting of fertile mantle at high pressures beneath the thick and cold Gondwanan lithosphere. Such conditions limited high-degree melting of peridotite sources which may have been predominant in the generation of the Karoo low-Ti basalts within lithospheric thinning zones. Primitive rocks that are related to continental flood basalts are rare, but often reveal crucial information on the ultimate sources of these huge outpourings of mantle-derived magma. Here we present mineral chemical data for mafic and ultramafic dikes from the Antarctic extension of the Jurassic (~180 Ma) Karoo continental flood basalt province that was emplaced during the initial stages ...